2017
DOI: 10.1016/j.msec.2016.11.129
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of sol-gel hydroxyapatite-titania composite and bilayer coatings

Abstract: Titania-Hydroxyapatite (TiO/HAP) reinforced coatings are proposed to enhance the bioactivity and corrosion resistance of 316L stainless steel (316L SS). Herein, spin- and dip-coating sol-gel processes were investigated to construct two kinds of coatings: TiO/HAP composite and TiO/HAP bilayer. Physicochemical characterization highlighted the bioactivity response of the TiO/HAP composite once incubated in physiological conditions for 7days whereas the TiO/HAP bilayer showed instability and dissolution. Biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 52 publications
(56 reference statements)
1
35
0
Order By: Relevance
“…From the 1980s until nowadays, a huge development in the sol-gel process was achieved. The research conducted allowed them to obtain OIH materials with applications in a wide range of areas, such as chemical and biosensors [13,85,86], in several transduction modes, from electrochemical [87][88][89][90][91] to optical [13,[92][93][94][95]; biomaterials for drug delivery [24,[96][97][98][99][100]; materials for improving bioactivity and biocompatibility of metallic substrates [101][102][103][104][105][106][107][108]; electronics [14]; environment [109][110][111]; optics [13,112,113]; medicine [53,[114][115][116][117]; functional smart coatings [31,38,73,118]; fuel and solar cells [119][120][121]…”
Section: Sol-gel Process: a Historical Perspective And Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 1980s until nowadays, a huge development in the sol-gel process was achieved. The research conducted allowed them to obtain OIH materials with applications in a wide range of areas, such as chemical and biosensors [13,85,86], in several transduction modes, from electrochemical [87][88][89][90][91] to optical [13,[92][93][94][95]; biomaterials for drug delivery [24,[96][97][98][99][100]; materials for improving bioactivity and biocompatibility of metallic substrates [101][102][103][104][105][106][107][108]; electronics [14]; environment [109][110][111]; optics [13,112,113]; medicine [53,[114][115][116][117]; functional smart coatings [31,38,73,118]; fuel and solar cells [119][120][121]…”
Section: Sol-gel Process: a Historical Perspective And Applicationsmentioning
confidence: 99%
“…However, such metallic alloys show some limitations, including low corrosion/wear resistance and unsuitable scratching and hardness properties. Therefore, to solve these drawbacks, several coatings have been proposed [57,101,105,108]. It was also concluded that zirconium-based coatings and OIH materials have been widely studied, as has the application, simultaneously, of polymers and zirconium enhanced several properties; namely, scratching, biocompatibility, bioactivity and hardness [53].…”
Section: Sol-gel Process: a Historical Perspective And Applicationsmentioning
confidence: 99%
“…Further studies are required to test the bioactivity and biocompatibility of these promising biomedical materials in vitro and in vivo. Recently, published work [62] has shown that the TiO 2 /HAP (20 vol pct TiO 2 ) composite coatings exhibited well biocompatible properties, stem cells attached well onto the surface, proliferated, and presented a polygonal morphology different from the fibroblastic-like morphology found on 316L SS. Moreover, TiO 2 /HAP composite improved the corrosion resistance of the 316L SS implant and showed mechanical properties close to that of hard tissue once incubated in physiological conditions for 7 days, highlighting its potential application in hard tissue replacement.…”
Section: E Mechanical Propertiesmentioning
confidence: 99%
“…10 The preparation of HA coating is one of the most important methods in surface modification techniques. Thus far, there have been many techniques to produce HA coating on implant surfaces, such as plasma spraying, 11 sol-gel techniques, 12 and electrophoretic deposition. 13 Unfortunately, these approaches usually require multiple steps, high temperature, special apparatus, and rigorous conditions that impede their application in the clinic.…”
Section: Introductionmentioning
confidence: 99%